The Mother's Day Mice - Bunting, Eve.; 1928-; Brett, Jan; 1949- (New York, 1986)
Three little mouse brothers go into the meadow to find a present for their mother but it is the littlest mouse that comes up with the most unusual gift of all.
Keywords: Gifts; Fiction; Mice; Fiction